2020
DOI: 10.1152/ajpendo.00321.2020
|View full text |Cite
|
Sign up to set email alerts
|

Differences in metabolic and liver pathobiology induced by two dietary mouse models of nonalcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a growing epidemic linked to metabolic disease. The first stage of NAFLD is characterized by lipid accumulation in hepatocytes, but this can progress into non-alcoholic steatohepatitis (NASH), cirrhosis, and hepatocellular carcinoma (HCC). Western diets, high in fats, sugars and cholesterol are linked to NAFLD development. Murine models are often used to study NAFLD; however, there remains debate on which diet-induced model best mimics both human disease progression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Impacts of 0.75% dietary cholesterol on hepatic inflammation and fibrosis are markedly increased when combined with poly-unsaturated fatty acids (PUFA), like ω6-PUFA from soybean oil [ 42 , 53 ], whereas this amount of added cholesterol also causes more severe steatosis, weight gain, and insulin resistance [ 43 ]. In comparison, we show that mice fed a high-fat/high-fructose diet supplemented with 2% cholesterol (40% kcal fat) have increased inflammation and fibrosis in liver, while obesity, insulin resistance and glucose intolerance are less pronounced compared to mice fed a similar diet without cholesterol [ 55 ]. Consistently, mice fed obesogenic diets with higher cholesterol levels, such as 1.25% and 2%, seem to exhibit similar impairments in weight gain [ 55 , 56 , 57 ].…”
Section: Cholesterol: a Question Of Quantity?mentioning
confidence: 99%
See 2 more Smart Citations
“…Impacts of 0.75% dietary cholesterol on hepatic inflammation and fibrosis are markedly increased when combined with poly-unsaturated fatty acids (PUFA), like ω6-PUFA from soybean oil [ 42 , 53 ], whereas this amount of added cholesterol also causes more severe steatosis, weight gain, and insulin resistance [ 43 ]. In comparison, we show that mice fed a high-fat/high-fructose diet supplemented with 2% cholesterol (40% kcal fat) have increased inflammation and fibrosis in liver, while obesity, insulin resistance and glucose intolerance are less pronounced compared to mice fed a similar diet without cholesterol [ 55 ]. Consistently, mice fed obesogenic diets with higher cholesterol levels, such as 1.25% and 2%, seem to exhibit similar impairments in weight gain [ 55 , 56 , 57 ].…”
Section: Cholesterol: a Question Of Quantity?mentioning
confidence: 99%
“…In comparison, we show that mice fed a high-fat/high-fructose diet supplemented with 2% cholesterol (40% kcal fat) have increased inflammation and fibrosis in liver, while obesity, insulin resistance and glucose intolerance are less pronounced compared to mice fed a similar diet without cholesterol [ 55 ]. Consistently, mice fed obesogenic diets with higher cholesterol levels, such as 1.25% and 2%, seem to exhibit similar impairments in weight gain [ 55 , 56 , 57 ]. Thus, too much cholesterol may counteract the goal of modeling liver damage within a setting of obesity and insulin resistance.…”
Section: Cholesterol: a Question Of Quantity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of a high-calorie diet with high fat and high sugar (western diet) results in weight gain and is the initial event for the development of fatty liver (125)(126)(127). Particular types of lipids and carbohydrates play important roles in the progression of NASH.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…After an additional 12 wk on this diet, histological analysis (based on hematoxylin and eosin staining) and a mean NAS score (± SE) of 6.2 ± 0.4 indicated that this modified diet induced histologic features characteristic of NASH with fibrosis (mean score ± SE: 1.40 ± 0.16), including micro- and macrovesicular steatosis, hepatocyte ballooning, and infiltration of inflammatory cells ( 30 ). In another study, the same diet was fed to both male and female C57BL/6N mice, and after 31 wk all mice had increased liver damage (hepatocyte ballooning, lobular inflammation) and fibrosis (F3–F4 for ≥50% of mice), but only mild weight gain and insulin resistance ( 31 ). Female mice were slightly slower to respond to the diet intervention, with normal concentrations of circulating ALT at week 12, but significantly elevated by week 24.…”
Section: Micementioning
confidence: 99%